Regulating a monopolist with uncertain costs without transfers - Manuel Amador; Kyle Bagwell (Theoretical Economics, 2022)
We analyze the Baron and Myerson (1982) model of regulation under the restriction that transfers are infeasible. Extending techniques from the delegation literature to incorporate an ex-post participation constraint, we report sufficient conditions under which optimal regulation takes the form of price-cap regulation. We establish conditions under which the optimal price cap is set at a level such that no types are excluded and show that exclusion of higher cost types can be optimal when these conditions fail. We also provide conditions for the optimality of price-cap regulation when an ex post participation constraint is present and exclusion is infeasible.
Keywords: L43; L5; D82; 330; delegation theory; price caps; Regulation